PENGARUH KINERJA, MOTIVASI, DAN KOMPENSASI TERHADAP DISIPLIN KERJA OUSOUCING UNIT ATMRC PT BNI PERSERO TBK KANTOR WILAYAH PALEMBANG - Gunawan Putrado; Fakhry Zamzam; Neny Rostiati (Integritas Jurnal Manajemen Profesional (IJMPRO), 2021)
The purpose of this study was to determine the effect, motivation and compensation on work discipline of employees of the Outsourcing Atmrc Unit of PT BNI Persero Tbk Palembang Regional Office partially or simultaneously. This research method uses survey and verification descriptives, field data collection uses questionnaires, interviews and documentation. This research is an associative research, where in this study there are variables that are related and can influence other variables. The population of this study were 62 employees of the BPKP Representative Office Auditor, South Sumatra Province. Data processing using SPSS 25 analysis tool. The results of the study stated that performance had an effect on work discipline, there was an effect of motivation on work discipline, compensation had an effect on work discipline. Performance, Motivation and Compensation affect Discipline simultaneously